Evidence for improved survival with bevacizumab treatment in recurrent high-grade gliomas: a retrospective study with ("pseudo-randomized") treatment allocation by the health insurance provider - Hofmann, Susanne; Schmidt, Manuel; Weissmann, Thomas; Eyüpoglu, Ilker Yasin; Strnad, Annedore; Semrau, Sabine; Fietkau, Rainer; Putz, Florian; Lettmaier, Sebastian (Journal of Neuro-Oncology, 2020)
Introduction Despite a large number of trials, the role of bevacizumab (BEV) in the treatment of recurrent high-grade gliomas is still controversial. Evidence regarding an effect on overall survival in this context is ultimately inconclusive. At the Department of Radiation Oncology at Erlangen, Germany we treated a large cohort of patients with recurrent gliomas where bevacizumab use was determined exclusively by the health care provider's approval of reimbursement. Methods 61 patients (between 06/2008 and 01/2014) with recurrent high-grade gliomas had reimbursement requests for BEV sent to their health insurance. 37 patients out of 61 (60.7%) had their requests approved and therefore received bevacizumab (BEV-arm) as part of their treatment. The remaining 24 (39.3%) patients received standard therapy without bevacizumab (non-BEV-arm). Survival endpoints were defined with reference to the first BEV request to the health insurance provider. Results Median overall survival (OS) for the whole cohort was 7.0 months. OS was significantly better for BEV vs. Non-BEV patients (median, 10.3 vs. 4.2 months, logrank p = 0.023). There was an increased BEV benefit in cases of higher-order recurrences (first order recurrence BEV vs. Non-BEV, 12.5 vs. 10.2 months, p = 0.578) (second or higher order of recurrence, 9.9 vs. 2.6 months, p = 0.010). On multivariate analysis for overall survival the prognostic impact of bevacizumab (HR = 0.43, p = 0.034) remained significant. Conclusion Our results suggest an influence of BEV on overall survival in a heavily pretreated patient population suffering from high-grade gliomas with BEV benefit being greatest in case of second or later recurrence.
CRIS-Team WoS Importer:2020-05-29